2021
DOI: 10.1002/jocc.12175
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Help‐Seeking Attitudes in College Student Service Members and Veterans

Abstract: We explored predictors of attitudes toward psychological help seeking among 103 student service members and veterans (SSM/V). Results showed that self‐stigma, public stigma, and gender significantly predicted attitudes toward psychological help seeking. A test of mediation revealed that self‐stigma fully mediated the relationship between public stigma and attitudes toward psychological help seeking. Implications for college counseling professionals who serve SSM/V are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Hence, instead of university type, intervention strategies should place more focus on other aspects that have been shown to significantly influence public stigma and help-seeking intention such as social health and mental health literacy (Aun et al, 2019;Yu et al, 2015). Next, it was found that public stigma awareness significantly influenced help-seeking intention, which is consistent with past findings (Noble, Platt & Leppma, 2021 Noor, 2019). However, this influence was no longer significant when public stigma endorsement is included into the regression analysis, which indicates a mediation effect.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Hence, instead of university type, intervention strategies should place more focus on other aspects that have been shown to significantly influence public stigma and help-seeking intention such as social health and mental health literacy (Aun et al, 2019;Yu et al, 2015). Next, it was found that public stigma awareness significantly influenced help-seeking intention, which is consistent with past findings (Noble, Platt & Leppma, 2021 Noor, 2019). However, this influence was no longer significant when public stigma endorsement is included into the regression analysis, which indicates a mediation effect.…”
Section: Discussionsupporting
confidence: 80%
“…Despite this fact, Malaysian undergraduate students are generally not prone to seek professional help for their mental health concerns (Salim, 2010). A common barrier for the utilisation of mental health services is stigma regarding mental health issues and services (Noble, Platt & Leppma, 2021;Ramli, Tilse & Wilson, 2017;Tay, Jaafar & Noor, 2019). This is especially true in the context of university students, where stigma is perceived as "only weak people seek mental health services" thus, leading the students to avoid attending psychological treatment even if they are in need for it (Kosyluk et al, 2021).…”
Section: Introductionmentioning
confidence: 99%